Influence of Color in a Lactation Room on Users' Affective Impressions and Preferences. (April 2019) - López-Tarruella, Juan; Llinares Millán, Carmen; Serra Lluch, Juan; Iñarra Abad, Susana; Wijk, Helle
Objective: The present study aims to examine the influence of environmental color hue in a lactation room at a health center on users' affective response and preference. Background: Hospital design plays an important role in the emotional experience of patients. In this regard, many studies have attempted to find relationships between design variables and healthcare facilities users' response. Color has been frequently examined because it is always present in the environment and can be easily changed. However, most of the studies dealing with color–emotion relationships acquire users' affective response by questionnaires developed by experts which could lead to inaccurate results since nonexperts may misunderstand concepts set by experts and use nonimmersive images to simulate the environments to assess. Methods: To overcome these limitations, a Kansei Engineering–based approach was proposed. In the first phase, users' specific affective factors for lactation rooms were determined using Semantic Differential. In the second phase, the influence of nine different color hues on users' affective factors was obtained. An immersive display system was used to visualize the room altering hues in an isolated and controlled way. Results: (1) Six user's affective factors connected to the lactation rooms were discovered: safety, elegance, coziness, spaciousness, simplicity, and luminosity, of which coziness has the most impact on the assessment of the room. (2) Warm colors like orange and yellow tend to score highly for coziness which puts them in leading positions when users' assess lactation rooms. Conclusions: Results provide recommendations for designers and show the advantages of using semantic differential and immersive displays to analyze user's affective response to environments.